Simulation of Industrialised Building System components production - Marsono, Abdul Kadir; Md. Tap, Masine; Ng, Soon Ching; Makhtar, Ahmad Mahir (2006)
The construction of IBS building should starts with the production of the IBS components and the production process is the main activity concerned in the IBS production plant. Having an optimum production line to manufacture the required IBS elements within targeted time and limited number of reusable steel mould is very important. In this study, workstation organization method has been adopted in the production of IBS component of beam and column. Witness 2001 simulation software has been used to model and simulate the most optimum production line set up. Here, two production lines set up have been proposed to complete the production of IBS beam and column between two and three months time with limited number of reusable steel mould to supply for the construction of medium size single storey IBS housing project ranging from 100 to 300 units. A contingency production line set up which able to complete the production of required IBS components within a month time with increased number of reusable steel mould has also been proposed. Number of resources such as workstation, tool, storage area and labour has been determined from the proposal. The proposed production line can be applied in the planning and cost estimating of IBS production plant set up.